2020
DOI: 10.21037/atm.2020.02.125
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of transcatheter arterial chemoembolization used with and without apatinib for intermediate- to advanced-stage hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Background: Hepatocellular carcinoma (HCC) is a common cancer worldwide and prognosis for patients with the disease remains poor. Most patients are diagnosed at an advanced stage and are only eligible for palliative therapy. As a novel vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor (VEGFR2-TKI), apatinib has a certain antitumor effect for a variety of solid tumors. In clinical practice, clinicians have attempted to treat intermediate-to advanced-stage HCC patients with a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
16
2
Order By: Relevance
“…HCC incidence has shown a global upward trend over the last decade ( Bertuccio et al, 2017 ), with approximately over 60% patients at an intermediate or advanced stage when newly diagnosed ( Yang et al, 2019 ). For this portion of patients, TACE or systemic treatment combined with targeted molecular inhibitors would yield better outcomes; for instance, multi-targeted tyrosine kinase inhibitors (TKIs) such as sorafenib and lenvatinib have benefited patients with advanced and unresectable HCC ( Forner et al, 2018 ; Yamada et al, 2020 ; Yoo et al, 2020 ; Zhao et al, 2020 ). Due to the shortcomings of chemotherapeutic agents for HCC, for example low response, intolerable side effects, and severe toxicity, it remains necessary to discover a novel agent or an optimized therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC incidence has shown a global upward trend over the last decade ( Bertuccio et al, 2017 ), with approximately over 60% patients at an intermediate or advanced stage when newly diagnosed ( Yang et al, 2019 ). For this portion of patients, TACE or systemic treatment combined with targeted molecular inhibitors would yield better outcomes; for instance, multi-targeted tyrosine kinase inhibitors (TKIs) such as sorafenib and lenvatinib have benefited patients with advanced and unresectable HCC ( Forner et al, 2018 ; Yamada et al, 2020 ; Yoo et al, 2020 ; Zhao et al, 2020 ). Due to the shortcomings of chemotherapeutic agents for HCC, for example low response, intolerable side effects, and severe toxicity, it remains necessary to discover a novel agent or an optimized therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, its incidence and mortality rate have kept rising in the latest decade, despite the advances in preventive measures, screening techniques, and diagnostic and therapeutic technologies ( Balogh et al, 2016 ; Hashim et al, 2016 ). Besides hepatic resection, liver transplantation and local ablation, transarterial chemoembolization (TACE) combined with radiotherapy, sorafenib, or chemotherapeutic agents (anthracyclines, mitomycin, and cisplatin) is commonly employed for patients with HCC as a liver-directed therapy ( Zhao et al, 2016 ; Kim and Den Abbeele, 2019 ; Zhao et al, 2020 ). However, HCC is usually resistant to chemotherapeutic agents in TACE or system chemotherapy ( Bruix et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a phase II clinical study reported that apatinib monotherapy could prolong the OS of advanced HCC patients (18). Considering its potential inhibitory role in post-TACE neo-angiogenesis, a series of studies have shown clinical benefits of TACE-apatinib in unresectable HCC compared with TACE-alone (19)(20)(21)(22)(23)(24). However, no previous comparison between TACE-apatinib and TACE-sorafenib has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous studies reported that TACE is beneficial for patients with advanced HCC (Bai et al, 2013;Choi et al, 2013;Zhao et al, 2013). Recently, an increasing number of studies have demonstrated that a combination of TACE with apatinib treatment (TACE-apatinib) may prolong the survival of selected patients with BCLC stage-C HCC (Lu et al, 2017;Yang et al, 2019;Zhao et al, 2020). To our best knowledge, there have been few reports regarding the use of TACE-apatinib as a treatment modality in advanced HCC patients with APS.…”
Section: Introductionmentioning
confidence: 99%